Fundamentals of Entrepreneurship (ENT 300) : Nur's Global Farming / Nur Suryati Mohamed Marzuki … [et al.] - Mohamed Marzuki, Nur Suryati; Rabihi, Nur Fajrina; Kamisly, Nurliyana Amira; Nuruddin, Nurhakim; Osen, Nurlydiaizzati (2010)
The Company's name chosen for our ETR300 group business proposal is "Nur's Global Farming". We have chosen that particular name as our identity because we have the desire to go globally when we are stable in terms of management and financially. "Nur's" represents all our partners' first names which also mean "light" in Islam. We have chosen Partnership as our business form due to more pros and cons as we compared before engaging into this business together.